Efficacy of Vasopressin-Methylprednisolone Vs Placebo for in-Hospital Cardiac Arrest: Systematic Review - Fatimah Fatimah; Alfino Alfino; Ghina Malya Darma; Aisyah Nur Fitri (Indonesian Journal of Global Health Research, 2025)
Intrahospital cardiac arrest (IHCA) has a high mortality (70-90%) despite standard resuscitation. The combination of vasopressin and methylprednisolone has been proposed as an adjuvant therapy to improve Return of Spontaneous Circulation (ROSC) and patient outcomes, but evidence of its effectiveness on long-term survival remains controversial. Objective to evaluate the efficacy of vasopressin-methylprednisolone combination versus placebo in IHCA patients for ROSC, survival, and neurologic outcomes. This systematic review study used the PICO framework (Population: Cardiac Arrest In-Hospital Patients; Intervention: Vasopressin + Methylprednisolone; Comparison: Placebo; Outcome: ROSC) and Randomized Controlled Trials (RCT) study design. A search in PubMed, ScienceDirect, and Google Scholar using the keywords "Vasopressin, Cardiac Arrest In-Hospital, Methylprednisolone, ROSC" resulted in a total of 769,070 initial articles. After screening based on access criteria, language, design, and publication year (2020-2025), 196 articles remained. Further eligibility selection based on sample suitability and specific interventions resulted in 41 potential articles. The final analysis to answer the question of the effect of the combination of Vasopressin and Methylprednisolone on ROSC found 3 RCT journals (from PubMed) that met all inclusion criteria. The combination of vasopressin-methylprednisolone significantly increased ROSC (42% vs. 33%; RR 1.30; 95% CI 1.03–1.63; *p* = 0.03), especially when given ≤8 minutes after cardiac arrest (51% vs. 35%). However, there were no significant differences in 30-day (9.7% vs. 12%; RR 0.83) or 1-year survival (6.3% vs. 8.3%; RR 0.76), favorable neurologic outcome (Cerebral Performance Category 1–2: 7.6% vs. 7.6%), or quality of life (EQ-5D-5L score). Adverse events (hyperglycemia, hypernatremia) were similar between groups. The combination of vasopressin-methylprednisolone effectively improves ROSC but has no impact on long-term survival or neurological recovery. Further studies are needed to identify subpopulations that benefit and explore post-ROSC therapeutic strategies.